De la mention de l’individu à celle du groupe : usage des expressions référentielles en fusion et en partition dans les récits d’enfants de 5 à 8 ans - Camille Dupret (Discours)
This study investigates children’s use of referring expressions in narratives when they express a referents grouping (i.e., fusion) and mention separate referents of an entity previously presented as a group (i.e., partition). As children seem to struggle to make a clear use of reference in narratives when different referents are candidate to be selected in discourse (Hickmann, 2002), this study aims to determine how they express the relations between a plural referring expression and its split antecedents within the discursive chain and, on the other hand, the forms they use to split several referents previously mentioned as a group. 45 children aged from 5 to 8 were video-recorded while recounting two different stories from textless sets of pictures. Results show that children use mostly pronominal forms in referents grouping, regardless of the distance of the antecedent, suggesting that referents grouping stands in continuity with the referential chains formed by the antecedents. However, older children of 7-8 years old seem to better use the established discursive universe to clarify the antecedents of plural referring expressions. In referents splitting, there is a greater variety of strong forms that express a contrast to the antecedents, but older children are more sensitive to distance from the antecedent in the choice of forms.